ANTIMICROBIAL EFFICACY OF ESSENTIAL OILS OF SELECTED PLANTS AND VACCINE DESIGN AGAINST mecA PROTEIN OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - Kaushik, Shuchi; Tomar, Rajesh Singh; Shrivastava, Vikas; Shrivastav, Archana; Jain, Sudhir Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective- Emergence of Multi Drug Resistance indicates a dire to understand the bacterial involvement in infections and find out new alternative approaches in its therapeutics and prevention. The present study was undertaken to study the antimicrobial resistance patterns of S. aureus isolated from various samples collected from Hospitals of Gwalior. During the present study an effort was made to find out the information about mecA protein of Staphylococcus and their conserved regions were analyzed in order to assess their antigenic potential. Methods- In the present study, a total of 872 samples were collected and processed for MRSA screening. Conventional methods were used for the isolation and identification of bacteria. Thereafter, antibacterial property of 20 various drugsÂ  as well as aromatic compounds of 18 herbal plants was performed against multiple resistant Staphylococcus aureus (MRSA) isolates according to the guidelines of National Committee for Clinical Laboratory Standards (NCCLS). In silico prediction of vaccine candidates in mecA through bioinformatics approach was also performed. Results-The study revealed that drug resistance pattern of MRSA isolates is increasing. But the major concern is the development of resistance against Vancomycin which is thought be the most effective drug against Staphylococcus. In comparison to antibiotics, essential oils showed very good activity against the test bacteria with few exceptions. Conclusion- The essential oils of Clove and Cinnamon were found to be more active against the test organism. We predicted multi-epitope peptide which was having very good potential to induce B cell response and a very good candidate for binding to MHC II molecule and thus can act as a suitable vaccine target against S. aureus. Keywords: Multidrug Resistance, essential oils, in silico, multi-epitope peptide.